2020
DOI: 10.3390/en14010019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Trade and Financial Globalization on Renewable Energy in EU Transition Economies: A Bootstrap Panel Granger Causality Test

Abstract: The globalized world has experienced significant environmental degradation together with raising global production and population. In this context, the employment of renewable energy use has become crucial for a sustainable environment and development. In the research, the mutual causality among renewable energy, trade and financial globalization, real GDP per capita, and CO2 emissions in EU transition economies experiencing the integration with global economy was explored through bootstrap panel Granger causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…In this study, we have measured green innovation through green technology patents as a core explanatory variable. While financial globalization is presented as the index computed by combining all the financial dimensions such as investment in FDIs, foreign reserves, investment agreements, investment restrictions, international income payments, debts, and so forth (Bayar et al, 2021). At the same time, environmental taxes are the revenue implemented as regulatory measures based on the theory of internalization of externalities (Wang & Huang, 2021).…”
Section: Data and Empirical Methodologymentioning
confidence: 99%
“…In this study, we have measured green innovation through green technology patents as a core explanatory variable. While financial globalization is presented as the index computed by combining all the financial dimensions such as investment in FDIs, foreign reserves, investment agreements, investment restrictions, international income payments, debts, and so forth (Bayar et al, 2021). At the same time, environmental taxes are the revenue implemented as regulatory measures based on the theory of internalization of externalities (Wang & Huang, 2021).…”
Section: Data and Empirical Methodologymentioning
confidence: 99%
“…In contrast, research on determinants of renewable energy consumption in Malaysia considering data for 1980-2015 [73] reveal no significant impact of CO 2 emissions on renewable energy. Bayar et al [74] found a unilateral causality from CO 2 emissions to renewable energy in Lithuania and Slovenia and a reciprocal causality between renewable energy and CO 2 emissions in Romania and Slovakia; however, they discovered no such effects in case of the other seven analyzed EU transition economies in the years 1995-2015.…”
Section: Control Variablesmentioning
confidence: 97%
“…Finally, according to Bayar et al (2021), the causality analysis revealed a unilateral causality from trade globalization to renewable energy in Estonia, Latvia, and Slovenia. Also, they found another causality from renewable energy to trade globalization in Croatia and Lithuania.…”
Section: The Granger Causality Testmentioning
confidence: 98%
“…Thus, identifying which variable causes the other allows greater clarity on the association's structure among the variables analyzed. Several studies have explored the relationship between the oil price and different variables and the impact of such relationships on the economic results (Behmiri and Pires Manso, 2012;Reboredo, 2018;Troster et al, 2018;Pirgaip and Dincergok, 2020;Bayar et al, 2021). They found empirical evidence of causality relationships running from crude oil price to crude oil consumption and GDP and a bidirectional causality relationship between crude oil consumption and GDP, both in the short and long runs.…”
Section: The Granger Causality Testmentioning
confidence: 99%